(untitled) (Bangladesh Journal of Child Health, 2018)
Neonatal hyperbilirubinemia is the most common clinical condition in the newborn requiring hospital readmission. About 60% of term and 80% of preterm infants develop jaundice during 1st week of life. Unconjugated hyperbilirubinemia occurs mostly due to increased hemolysis, decreased hepatic clearance, enterohepatic circulation, immaturity, blood group incompatibility and infections. Evaluation of neonatal jaundice is done based on history, age of onset of jaundice and physical examination findings which is necessary for proper management. Otherwise significant hyperbilirubinemia may endanger life of the baby and may lead to acute and subsequently chronic bilirubin encephalopathy. There are many diagnostic tools those help to detect jaundice such as Kramer’s rule, transcutaneous bilirubinometer, Bilichecker apps and smartphone apps. Besides these BIND score added a new dimension in diagnosis of acute bilirubin encephalopathy which can be confirmed by measuring bilirubin – albumin ratio in blood. Management of unconjugated hyperbilirubinemia includes: Phototherepy, Exchange transfusion are two major effective therapeutic modalities available today. Additional options include Pharmacotherapy in the form of phenobarbital and intravenous immunoglobulin. Each therapy has its pros and cons. Even there is dilemma in many therapeutic conditions like role of prophylactic phototherapy in preterm neonates, role of sunlight etc. As pediatricians have to deal cases with unconjugated hyperbilirubinemia frequently, so an updated knowledge is required. From this concern we reviewed issues on neonatal unconjugated hyperbilirubinemia and compiled for better understanding of the condition. Bangladesh J Child Health 2018; VOL 42 (1) :30-37